Activity of TNT: a phase 2 study using talimogene laherparepvec, nivolumab and trabectedin for previously treated patients with advanced sarcomas (NCT# 03886311) - Chawla, Sant P.; Tellez, Walter Andree; Chomoyan, Hripsime; Valencia, Chrysler; Ahari, Amir; Omelchenko, Nadezhda; Makrievski, Stefan; Brigham, Don A.; Chua-Alcala, Victoria; Quon, Doris; Moradkhani, Ania; Gordon, Erlinda M. (Frontiers in Oncology, 2023)
Background: Intratumoral injection of talimogene laherparepvec has a local oncolytic effect and evokes a cytotoxic immune response. Therefore, the combination of talimogene laherparepvec with trabectedin and nivolumab may have synergistic effects with no added toxicity in advanced sarcoma. Patients and Methods: This single center, single arm phase 2 trial was conducted from May 30, 2019 to January 31, 2022. Endpoints: Primary: Progression-free survival (PFS) rate at month 12. Secondary: Best overall response, progression free survival rate rate at 6 and 9 months, overall survival rate at 6, 9, and 12 months, incidence of conversion of an unresectable tumor to a resectable tumor, and incidence of adverse events. Eligible patients had to be > 18 years of age, have progressed advanced histologically proven sarcoma, at least 1 previous chemotherapy regimen, and at least one accessible tumor for intratumoral injection. Treatment: Trabectedin intravenously (1.2 mg/m2 q3 weeks), nivolumab intravenously (3 mg/kg q2 weeks), and intratumoral talimogene laherparepvec (1x108 PFU/ml q 2 weeks). Results: Median time of follow-up: 15.2 months (IQR: 6.67 to 24.14). Per protocol, 39 patients were evaluable for efficacy analysis. These patients had completed at least one treatment cycle and had a follow-up CT scan. Median number of prior therapies: 4 (range 1-11). Progression free survival rate at month 12, 36.7%. Confirmed best Overall Response by RECIST v1.1 = 4 PR, 29SD, 6PD (Rate 10.2%). Disease control rate, 84.6%; median PFS, 7.8 (95%CI: 4.1-13.1) months; 6-, 9-, 12-month PFS rates, 54.5% / 45.9% / 36.7%; median overall survival (OS) 19.3 (95%CI: 12.8 - .); 6-, 9- and 12-month OS rate, 86.9% / 73.3% / 73.3%. One patient had complete surgical resection. Fifty percent of patients had a >=grade 3 treatment related adverse events which include anemia (6%), thrombocytopenia (6%), neutropenia (4%), increased ALT (4%), increased GGT (4%), decreased LVEF (4%), dehydration (4%), hyponatremia (4%). Conclusions: Taken together the data suggests that the TNT regimen is effective and safe for advanced previously treated sarcoma. Therefore, the TNT regimen is worth being further studied in a randomized phase 3 trial as first- or second- line treatment for patients with advanced sarcoma.